Genomic Analysis Reveals That Isolation Temperature on Selective Media Introduces Genetic Variation in Campylobacter jejuni from Bovine Feces - Sicun Fan; Derek Foster; Shaohua Zhao; Sampa Mukherjee; Yesha Shrestha; Cameron Parsons; Sophia Kathariou (Pathogens, 2022)
Campylobacter jejuni is commonly isolated on selective media following incubation at 37 °C or 42 °C, but the impact of these temperatures on genome variation remains unclear. Previously, Campylobacter selective enrichments from the feces of steers before and after ceftiofur treatment were plated on selective agar media and incubated at either 37 °C or 42 °C. Here, we analyzed the whole genome sequence of C. jejuni strains of the same multilocus sequence typing (MLST)-based sequence type (ST) and isolated from the same sample upon incubation at both temperatures. Four such strain pairs (one ST8221 and three ST8567) were analyzed using core genome and whole genome MLST (cgMLST, wgMLST). Among the 1970 wgMLST loci, 7–25 varied within each pair. In all but one of the pairs more (1.7–8.5 fold) new alleles were found at 42 °C. Most frameshift, nonsense, or start-loss mutations were also found at 42 °C. Variable loci CAMP0575, CAMP0912, and CAMP0913 in both STs may regularly respond to different temperatures. Furthermore, frameshifts in four variable loci in ST8567 occurred at multiple time points, suggesting a persistent impact of temperature. These findings suggest that the temperature of isolation may impact the sequence of several loci in C. jejuni from cattle.